Carbonated nanohydroxyapatite from bone waste and its potential as a super adsorbent for removal of toxic ions. Issue 2 (April 2021) - Sekine, Yurina; Nankawa, Takuya; Yamada, Teppei; Matsumura, Daiju; Nemoto, Yoshihiro; Takeguchi, Masaki; Sugita, Tsuyoshi; Shimoyama, Iwao; Kozai, Naofumi; Morooka, Satoshi
Abstract: The effective, low-cost decontamination of toxic metals is critical for addressing global health risks, reducing environmental pollution, and building a sustainable future. Here, we developed an eco-friendly hydroxyapatite nanocrystal adsorbent made from bone waste that can effectively capture 90 Sr. Highly carbonated nanohydroxyapatite (C-NHAP) crystals with a negatively charged surface were obtained by simply immersing pig bone in an aqueous solution of sodium hydrogen carbonate (NaHCO3 ). Fourier transform infrared spectra showed that the C-NHAP was highly carbonated and that the amount of introduced carbonate ions (CO3 2− ) increased with increasing NaHCO3 concentration in the immersion solution. With increasing amount of CO3 2− ions introduced into the C-NHAP, it exhibited a greater ion-adsorption performance. The distribution coefficient ( K d  = 24, 780 mL g −1 ) of the C-NHAP for Sr 2+ was approximately 20 and 250 times greater than those of clinoptilolite and untreated bone, respectively. The C-NHAP also exhibited high adsorption capacity ( Q e  = 125 mg g −1 ) for Sr 2+ . The extended X-ray absorption fine structure spectra showed that the CO3 2− sites in C-NHAP played an important role in its high adsorption performance. The C-NHAP exhibited high adsorptivity for Cd 2+, Pb 2+, and Cu 2+ . The C-NHAP prepared from bone waste is an eco-friendly, high-performance, low-cost material that should be useful in environmental pollutant removal and food waste disposal. Graphical Abstract: ga1 Highlights: Highly carbonated nanohydroxyapatite (C-NHAP) adsorbent was prepared from bone waste. The C-NHAP exhibited high adsorption properties for Sr 2+, Cd 2+, Pb 2+, and Cu 2+ . The higher the CO3 2− ratio of C-NHAP, the higher will be the Sr 2+ adsorptivity. The C-NHAP prepared from bone waste is an eco-friendly and low-cost material.